Development of tuberculosis pocket book and dental health and mouths for parents of children with tuberculosis in Tasikmalaya City - Dewi, Tita Kartika; Kamelia, Emma; Triyanto, Rudi; Dadang, Abdullah Mubarok (Science Midwifery, 2024)
Tuberculosis is a chronic infectious disease that attacks various organs, including the lungs. Tuberculosis can also attack other organs, such as joints, bones, brain membranes, and the oral cavity is no exception. Oral tuberculosis provides a varied clinical picture, such as ulcers (canker sores), nodules (lumps), inflammation of the gums, and the lesions may or may not cause pain. According to the Tasikmalaya City Health Office, the number of TB patients in children as of March 2023 amounted to 503, with the age category of 0-5 years 254, 6-14 years 249. The Purpose of the Research: to produce a pocket book about tuberculosis and dental and oral health for parents of children with tuberculosis in Tasikmalaya City. Research Method: Research and Development (R&D) research method by collecting references for research materials, summarizing data by conducting FGD with tuberculosis program holders and dental and oral health program holders from the Tasikmalaya City Health Office and 22 health centers in the Tasikmalaya City Health Office area with 60 respondents, compiling pocket book products. Research Result: The description of the conclusion to the respondents' answers was the development of a pocket book on tuberculosis and dental and oral health for parents of children with tuberculosis in Tasikmalaya City. Conclusion: This study produced a pocket book about tuberculosis and dental and oral health for parents of children with tuberculosis.